2022
DOI: 10.1155/2022/1951014
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Glycerylphosphorylcholine and D-Panthenol Eye Drops in Patients Undergoing Cataract Surgery

Abstract: Cataract surgery is widespread. The surgical procedure is associated with damage to the epithelial barrier and interruption of the corneal innervation. In addition, pathological events sustain signs and symptoms that may persist for a long time. Recently, a fixed combination of alpha-glycerylphosphorylcholine and D-Panthenol (Oftassiale) has been available as eye drops. The present study investigated the effects of an Oftassiale therapy in 20 patients undergoing cataract surgery. A comparison group included 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In this study, dexpanthenol/alphaglycerylphosphorylcholine (Oftassiale ® , DMG, Italy) was applied to the study group, while sodium hyaluronate was applied to the control group for 1 month after cataract surgery; the dexpanthenol/alphaglycerylphosphorylcholine group had higher postoperative subbasal nerve plexus density, with fewer bead-like formations. 31 Similarly, coenzyme Q10 and trehalose/sodium hyaluronate eye drops have provided rapid nerve healing after cataract surgery. 32,33 Another leading cause of DED after cataract surgery is OSI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, dexpanthenol/alphaglycerylphosphorylcholine (Oftassiale ® , DMG, Italy) was applied to the study group, while sodium hyaluronate was applied to the control group for 1 month after cataract surgery; the dexpanthenol/alphaglycerylphosphorylcholine group had higher postoperative subbasal nerve plexus density, with fewer bead-like formations. 31 Similarly, coenzyme Q10 and trehalose/sodium hyaluronate eye drops have provided rapid nerve healing after cataract surgery. 32,33 Another leading cause of DED after cataract surgery is OSI.…”
Section: Discussionmentioning
confidence: 99%
“…33,35 In a previous study using dexpanthenol/alpha-glycerylphosphorylcholine drops, activated keratocyte and langerhans cell infiltrations were observed, particularly at the incision sites 1 month after surgery, and no difference was reported between study and control groups. 31 In another study, Cagini et al compared the efficacy of trehalose/sodium hyaluronate eye drops to a single dose of sodium hyaluronate in the treatment of postoperative DED and observed a statistically significant decrease in langerhans cell count, degree of keratocyte activation, nerve tortuosity, and reflectivity with trehalose/sodium hyaluronate eye drops. 33 In our study, we also observed a significant reduction in the number of dendritic cells, activated keratocytes, and the degree of nerve tortuosity, which are all indicators of OSI.…”
Section: Discussionmentioning
confidence: 99%